Endothelial expression of JCAD worsens outcome after acute ischemic stroke: a translational study. (3rd October 2022) - Ministrini, S; Liberale, L; Beer, G; Puspitasari, Y M; Schwarz, L; Niederberger, R; Katan Kahles, M; Bacigaluppi, M; Akhmedov, A; Montecucco, F; Luescher, T F; Camici, G G
Abstract: Introduction: Despite the increasing availability of early reperfusion, acute ischemic stroke (AIS) is still burdened by high mortality and long-time disability. Junctional protein associated with Coronary Artery Disease (JCAD) was associated to multiple cardiovascular disorders, but its role in AIS has not been investigated so far. Purpose: To investigate the role of endothelial JCAD in the pathogenesis of AIS and its potential as a therapeutic target. Methods: Cerebral ischemia was induced by transient Middle Cerebral Artery Occlusion (tMCAO) in mice with either global or endothelial-specific JCAD genetic deletion, and littermate controls. Stroke size was assessed ex-vivo by tetrazolium chloride staining 48 hours after reperfusion. For neurological assessment, RotaRod Test and Bederson score were recorded 24 and 48 hours after reperfusion. In vivo silencing of JCAD was achieved by intravenous injection of a JCAD small interfering RNA (siRNA) after tMCAO. In parallel, JCAD silencing was performed in vitro in human brain microvascular endothelial cells (HBMVECs) using siRNA transfection, followed by hypoxia/reoxygenation (H/R) injury. Cell death and trans-endothelial electrical resistance (TEER) were measured by LDH assay and electrical cell-substrate impedance sensing, respectively. Molecular mechanisms were investigated in vivo by immunohistochemistry and in vitro by Western blot, respectively. Lastly, JCAD plasma levels were measured by ELISA in two independent cohorts of patients with AIS. Results: The expression of JCAD was up-regulated in the ipsilateral hemisphere of stroke in wild-type mice. Both global and endothelial-specific JCAD knockout mice displayed reduced stroke size after tMCAO and a significantly improved Bederson score. Similarly, mice with post-ischemic JCAD silencing had a reduced stroke size and a better motor performance at the RotaRod test (Figure 1). In vitro, JCAD-silenced HBMVECs showed a reduced cell death rate and a higher TEER after H/R injury, compared to controls. JCAD-silenced HBMVECs also had an increased phosphorylation of Akt. After treatment with the Akt/PI3K inhibitor Wortmannin, JCAD-silenced HBMVECs showed similar TEER and cell death rates to non-silenced cells, following H/R (Figure 2). Lastly, an increase of circulating levels of JCAD was observed in patients with AIS within 24 hours from symptoms onset. Furthermore, higher levels of JCAD at the time of hospitalization were associated with a higher risk of death within 90 days after the event. Conclusions: JCAD expression is associated with a larger brain damage in mice in vivo and with a higher mortality in patients. In vitro results suggest that JCAD plays a pivotal role in regulating the integrity of endothelium after a H/R injury, inducing cellular death through the inhibition of the Akt/PI3K pathway. Thus, post-ischemic silencing of JCAD may represent a therapeutic strategy to improve the prognosis of patients with acute ischemic stroke. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Swiss National Science Foundation